Repeated recurrence of a gastric gastrointestinal stromal tumor on the chest wall after initial curative resection: Report of a case. (2015) - Iwatsuki, Masaaki; Takamori, Hiroshi; Eto, Kojiro; Shimizu, Kenji; Ogawa, Katsuhiro; Yamamura, Kensuke; Ozaki, Nobuyuki; Tanaka, Hideyuki; Sugiyama, Shinichi; Ogata, Kenichi; Doi, Koichi; Kamio, Takihiro; et al.
Highlights: Extra-abdominal recurrence or metastasis of a GIST is very rare. Furthermore, most GISTs recur during the first 5 years of follow-up and few recur after the first 10 years of follow-up. We herein report a case of repeated recurrence of gastric GIST involving the chest wall of a patient 11 years after curative resection. Abstract: Introduction: Extra-abdominal recurrence or metastasis of a gastrointestinal stromal tumor (GIST) is very rare. Chest wall recurrence of a resected gastric GIST is extremely rare. Presentation Of Case: A 64-year-old Japanese man had undergone proximal gastrectomy for a gastric submucosal tumor 11 years previously. The histopathological diagnosis was GIST (size, 8 cm). He did not receive adjuvant therapy, and underwent imaging evaluations every 6 months for the first 5 years after surgery and then annually. He was admitted to our hospital because of a lump on his right anterior chest wall 7 years after curative resection. We resected the tumor, and histopathologic findings revealed metastatic GIST. Four years after metastasectomy, another lump appeared at a different location on the right anterior chest wall. The patient was diagnosed with a second recurrence of gastric GIST and began adjuvant treatment with imatinib after second resection. He has remained alive without tumor recurrence for 2 years. Discussion: Most recurrences were predominantly found in the intra-abdominal cavity, either locally or involving the liver or peritoneum. Extra-abdominal recurrence was much less common. Although we assume that the recurrent tumor of our patient was derived from his gastric GIST, based on the histopathological examinations and clinical course, it is possible that the recurrent tumor of our case was an "extragastrointestinal GIST". Conclusion: Because extra-abdominal recurrence can occur many years after curative resection, continued, careful whole-body follow-up is required for patients with high-risk GIST.